Change your Angle of View Sinusoidal C-Arm Movement in Cranial Flat-panel CT to Improve Image Quality - Lücking, Hannes; Hölter, Philip; Lang, Stefan; Schmidt, Manuel; Eisenhut, Felix; Dörfler, Arnd (Clinical Neuroradiology, 2022)
Background Artifacts from surrounding bony structures, especially from the petrous bones, regularly impair soft tissue computed tomography (CT) imaging of the middle and posterior fossa. This affects flat-panel CT in particular. Sinusoidal movement of the C-arm during acquisition (i.e. craniocaudal tilting along with semicircular rotation) is supposed to reduce artifacts, thus enhancing soft tissue imaging quality. Methods In the work-up of ischemic stroke or subarachnoid hemorrhage 40 patients underwent multi-slice CT (MS-CT) and either plain circular (cFP-CT; n = 20) or sinusoidal (sFP-CT; n = 20) flat-panel CT within a short interval. Two independent readers analyzed MS-CT and FP-CT datasets for recognizability of eight different brain structures and three typical types of artifacts according to a predetermined score. Results Interrater reliability was moderate for cFP-CT (kappa = 0.575) and good to very good for ratings of MS-CT and sFP-CT (kappa = 0.651 to kappa = 1). MS-CT was rated to be significantly better than cFP-CT and sFP-CT (p < 0.0001) in the overall score. Yet, sFP-CT was rated to be significantly superior to cFP-CT (overall p < 0.0001) regarding most anatomical regions and petrous bone artifacts. Conclusion Compared to a standard circular protocol, sinusoidal C-arm movement in cranial FP-CT can significantly reduce artifacts in the posterior fossa and, moreover, can improve visualization of most supratentorial and infratentorial anatomical structures.
CRIS-Team WoS Importer:2022-05-20